2108. Perfluorocarbon Omniphobic Treatment Prevents Bacterial Colonization of Urinary Catheter in a Rat Model. (26th November 2018) - Badv, Maryam; El Sayed, Faten; Faugeroux, Julie; Behr-Roussel, Delphine; Rottman, Martin; Didar, Tohid
Abstract: Background: The bacterial colonization of urinary catheters is a major source of hospital acquired urinary tract infections (HAUTI). Bacteria repellent coatings could lower HAUTI prevalence and minimize antimicrobial usage. We report a model of spontaneous bacterial colonization of an intravesical catheter in a spinalized rat model, and the first in vivo proof of the efficacy of lubricant-infused catheters (LICs) in preventing bacterial colonization. Methods: LICs preparation: Oxygen plasma treated polyethylene catheters were immediately placed in a vacuum desiccator and 200 µL of trichloro (1 hour, 1H, 2H, 2H-perfluorooctyl) silane) was placed beside the catheter segments. The vacuum pump connected to the desiccator was turned on with the exit valve closed once a pressure of −0.08 MPa was achieved. The chemical vapour deposition process was initiated for 4 hours. Catheters were removed from the desiccator and placed in an oven at 60 o C for a minimum of 12 hours in order to complete the modification process. Catheters were saturated with a biocompatible fluorocarbon-based lubricant (perfluorodecalin) prior to implantation. Thirty centimeters long native catheters and LICs were surgically implanted in the bladder of rats spinalized 19 days prior and programmed to undergo cystometry experiments 48 hours later. Each rat was maintained individually in a cage with food and water ad libitum until bladder functional evaluation, and benefitted from a of trimethoprim sulfadoxine and fluoroquinolone prophylaxis. At the end of the cystometry experiments, the animals were euthanized and the bladder catheter was removed. A 1 cm section from the intravesical end of the catheter was cut and placed in 1 mL of Amies medium (eSawb, Copan), vortexed and sonicated. Ten microliters of the suspension were plated on URIselect4 medium (Bio-Rad, Hercules, Ca) for bacterial enumeration. Results: A significant reduction in bacterial colonization with Enterobacteriaceae and Enterococci was observed in the LICs group ( N = 6, below 100 CFU threshold) compared with the native catheter group ( N = 5, average 8200 CFU) ( P < 0.02). Conclusion: Lubricant-infused catheters effectively prevent bacterial colonization in vivo and provide an attractive and nonselective option for HAUTI prevention. Disclosures: All authors: No reported disclosures.